Mengeksplorasi Relief dan Rerajahan dalam Penciptaan Seni Rupa - Sedana, I Gusti Ngurah Agung Putra Wahyu; Wirakesuma, I Nengah; Mudana, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2026)
The Merdeka Belajar Kampus Merdeka (MBKM) program is a policy of the Ministry of Education and Culture aimed at encouraging students to master various fields of knowledge as preparation for entering the professional world. At ISI Denpasar, the MBKM program this year is implemented in collaboration with industry partners in the fields of art, design, creative industries, and culture. This research originates from the idea of creating visual artworks inspired by reliefs and rerajahan. Reliefs, as two- and three-dimensional carvings found in Balinese temples, hold strong historical, religious, and artistic values, although some have been diminished due to renovations that neglect the original ornamentation. Meanwhile, rerajahan represents magical and spiritual symbols in Balinese Hindu traditions, enriched with sacred modre characters believed to possess divine energy. The creative process was carried out through literature review, observation of temple reliefs, and visual exploration of modern scripts in rerajahan. The outcomes consist of two-dimensional artworks (paintings) and three-dimensional ornamentations that integrate the form of reliefs with the symbolic strength of rerajahan, using expressionist and impressionist approaches to reinterpret traditional forms. The implication of this work shows that combining reliefs and rerajahan can create contemporary artistic expressions rooted in tradition while also contributing to the preservation of Balinese cultural, historical, spiritual, and aesthetic values.